(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article presents an report of the experiences of the catarinense group Eranos Círculo de Arte in the use of digital projection in performing arts. Approaches the three premises defended by the group for expressive amplification of this tool: 1) digital projection is light, 2) the relationship with something alive, and 3) the interdependence between human and digital for the realization of the scene. It parallels the concept of light-character and animation theater, and relates its premises to the group’s practice in the construction of the theatrical rite.